Pharmacological Evidence That Dopamine Inhibits the Cardioaccelerator Sympathetic Outflow via D2-Like Receptors in Pithed Rats - Oscar Alcántara-Vázquez; Ma. Trinidad Villamil-Hernández; Araceli Sánchez-López; David Centurión (Elsevier, 2013)
It has been suggested that N,N-di-n-propyl-dopamine (dopamine analogue) decreased heart rate in rats through stimulation of dopamine receptors. Nevertheless, the role of prejunctional dopamine D1/2-like receptors or even α2-adrenoceptors to mediate cardiac sympatho-inhibition induced by dopamine remains unclear. Hence, this study identified the pharmacological profile of the cardiac sympatho-inhibition to dopamine in pithed rats. Male Wistar rats were pithed and prepared to stimulate the cardiac sympathetic outflow or to receive i.v. bolus of exogenous noradrenaline. I.v. continuous infusions of dopamine (endogenous ligand) or quinpirole (D2-like agonist) dose-dependently inhibited the tachycardic responses to sympathetic stimulation, but not those to exogenous noradrenaline. In contrast, SKF-38393 (100 μg/kg∙min, D1-like agonist) failed to modify both of these responses. The sympatho-inhibition to dopamine (1.8 μg/kg∙min) or quinpirole (100 μg/kg∙min): i) remained unaltered after saline or the antagonists SCH-23390 (D1-like, 300 μg/kg) and rauwolscine (α2-adrenoceptors, 300 μg/kg); and ii) was significantly antagonized by raclopride (D2-like, 300 μg/kg). These antagonists, at the above doses, failed to modify the sympathetically-induced tachycardic responses. The above results suggest that the inhibition of the cardiac sympathetic outflow to dopamine and quinpirole is primarily mediated by prejunctional D2-like receptors but not D1-like receptors or α2-adrenoceptors. Keywords:: D2-like receptor, dopamine, sympatho-inhibition, pithed rat, tachycardia